Connecting tourists to musical destinations: The role of musical geographical imagination and aesthetic responses in music tourism. (October 2023) - Zhuang, Min; Zhang, Honglei; Li, Peizhe; Shen, Caiyun; Xiao, Xiao; Zhang, Jie
Abstract: While the value of music in connecting tourists to destinations is recognized, its mechanism remains unclear. This study adopts aesthetic responses to explore how musical geographical imagination influences tourists' place bonding and subsequent behavioral intentions. This explanatory sequential mixed-methods study: 1) elucidates the connotation and effects of musical geographical imagination integrating with aesthetics in tourism research; 2) shows that tourists' aesthetic cognitive and affective responses to musical geographical imagination strengthen place bonding, and buttresses the importance of affective responses in leveraging behavioral intentions; and 3) indicates that tourists' responses to musical stimuli differ in direct and indirect destination experience contexts, demonstrating that musical stimulus context moderates on associations of imagination with cognitive responses, and affective responses with behaviroal intentions. This study empirically expands the imagination from individual auditory spaces to a destination and advances tourism aesthetics research; it guides using music in tourism sensory marketing and tourism soundscape design.